Analysis of Voluntary Counseling and Testing (VCT) Service Utilization Factors in Tuberculosis (TB) Patients in Semarang City - Erli Widiastuti; Widya Hary Cahyati; Sri Ratna Rahayu (PROMOTOR, 2024)
Tuberculosis (TB) is an infectious disease caused by Mycobacterium Tuberculosis and is the leading cause of health problems and the most common cause of death worldwide. Tuberculosis is the disease that causes the most health problems in the community to date. Based on data from the Semarang City Health Office, it is known that 41.4% of tuberculosis patients will undergo Voluntary Counseling and Testing (VCT) screening in 2022. This is of course still below the screening target, which is the 100% target. Mismatch with VCT screening targets in TB patients can occur due to fear and anxiety if TB patients know their health status related to HIV and AIDS. This study was prepared using a cross-sectional design. The number of respondents included is 107 people diagnosed with TB at Kedungmundu, Bangetayu, and Tlogosari Wetan Health Centers in 2023. Univariate and Bivariate analyses were used to analyze the results of this study. The results of this study found that variables consisting of age, marital status, and education had no relationship with the use of VCT services in tuberculosis (TB) patients in Semarang City.